2021
DOI: 10.1177/1461444820954201
|View full text |Cite
|
Sign up to set email alerts
|

Sharing and storing digital cultural records in Central Australian Indigenous communities

Abstract: This article considers how Indigenous peoples in Central Australia share and keep digital records of events and cultural knowledge in a period of rapid technological change. To date, research has focused upon the development of digital archives and platforms that reflect Indigenous epistemologies and incorporation of protocols governing access to information. Yet there is scant research on how individuals with little access to such media share and hold—or not, as the case may be—digital cultural information. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…This may range from simply asking a nurse or parent how they and their child are doing, to educating oneself on a family’s specific cultural background. Awareness of religious practices or cultural factors that prohibit the use of electronics, or in some way impact the collection or use of such recordings, for example, shows families that study staff respect their needs (Kulkarni et al, 2014; Nevins, 2012; Vaarzon-Morel et al, 2021). Offering to suspend recording during a parent or child’s mental or physical crisis also demonstrates that the research team cares about and prioritizes their well-being.…”
Section: Discussionmentioning
confidence: 99%
“…This may range from simply asking a nurse or parent how they and their child are doing, to educating oneself on a family’s specific cultural background. Awareness of religious practices or cultural factors that prohibit the use of electronics, or in some way impact the collection or use of such recordings, for example, shows families that study staff respect their needs (Kulkarni et al, 2014; Nevins, 2012; Vaarzon-Morel et al, 2021). Offering to suspend recording during a parent or child’s mental or physical crisis also demonstrates that the research team cares about and prioritizes their well-being.…”
Section: Discussionmentioning
confidence: 99%
“…We also searched Aboriginal language dictionaries, unpublished and published narratives, photo and film archives and other repositories (Ethnographic data; https://doi.org/10.26182/k3p0-hf57). Archival records and digital infrastructure hold substantive cultural information 83 . Tertiary sources in published ethnographies, biographies and more have been found.…”
Section: Ethnographic Methodsmentioning
confidence: 99%
“…An example from Australia was shared by Sunderland, who suggested that online musical engagements and recording could be understood as a form of musical care for First Nations musicians who have experienced ongoing marginalization and lack of access to resources to record and share their music (see also Budrikis & Bracknell, 2022; Marett & Barwick, 2003; Vaarzon-Morel et al, 2021). These examples indicate the diversity of forms that musical care may take, the ways in which it may respond to structural inequalities and histories of racism and colonization, and the significance of context in understanding musical care.…”
Section: Musical Care As Context-dependent and Socialmentioning
confidence: 99%